A comparison of extraction procedures for water‐extractable organic matter in soils. (9th June 2014) - Guigue, J.; Mathieu, O.; Lévêque, J.; Mounier, S.; Laffont, R.; Maron, P. A.; Navarro, N.; Chateau, C.; Amiotte‐Suchet, P.; Lucas, Y.
Summary The characteristics of dissolved organic matter (DOM) in soils are often determined through laboratory experiments. Many different protocols can be used to extract organic matter from soil. In this study, we used five air‐dried soils to compare three extraction methods for water‐extractable organic matter (WEOM) as follows: (i) pressurised hot‐water‐extractable organic carbon (PH‐WEOC), a percolation at high pressure and temperature; (ii) water‐extractable organic carbon (WEOC), a 1‐hour end‐over shaking; and (iii) leaching‐extractable organic carbon (LEOC), a leaching of soil columns at ambient conditions. We quantified the extraction yield of organic carbon; the quality of WEOM was characterized by UV absorbance, potential biodegradability (48‐day incubation) and parallel factor analysis (PARAFAC) modelling of fluorescence excitation emission matrices (FEEMs). Biodegradation of dissolved organic carbon (DOC) was described by two pools of organic C. The proportions of labile and stable DOC pools differed only slightly between the WEOC and LEOC methods, while PH‐WEOC contains more stable DOC. The mineralization rate constants of both labile and stable DOC pools were similar for the three methods. The FEEMs were decomposed into three components: two humic‐like fluorophores and a tryptophan‐like fluorophore. The effect of extraction method was poorly discriminant and the most similar procedures were PH‐WEOC and LEOC while WEOC extracts were depleted in humic‐like fluorophores. This study demonstrates that WEOM quality is primarily determined by soil characteristics and that the extraction method has a smaller, but still significant, impact on WEOM quality. Furthermore, we observed considerable interaction between extraction procedure and soil type, showing that method‐induced differences in WEOM quality vary with soil characteristics.